Home hospitalization in Portugal. A new field of action in the hospital's Social Work: https://doi.org/10.53809/2021-01-TS-n.1-188-207 ("Temas Sociais" Journal, 2021)
The present article intends to make known social service intervention practices in the Unidade de Hospitalização Domiciliária (Home Hospitalization Unit) (UHD) of the Centro Hospitalar Universitário de Lisboa Central (CHULC), as well as caracterize the treated patients and social responses within the framework of home hospitalization. This is a study of quantitative approach, of the descriptive and exploratory type. Between May of 2019 and May of 2020, 232 patients were evaluated for admission in the UHD of the CHULC, of which 122 were excluded for several reasons and 110 patients were treated. Of the treated patients in home hospitalization, 28 required the social worker's intervention. The data was collected through the analysis of the social processes, obtained by the records of the social worker's analysis in the computer programs “SAAS” (Sistema de Apoio ao Assistente Social) and “SClínico” and a specific record sheet was created in order to collect the following parameters: the patient's profile, reasons for exclusion, social diagnosis and the social responses that were put into action. The results of this analysis allow us to verify that the social worker's intervention in the UHD is irreplaceable, fundamental and determinant in the support for the patient and their family and in the quality of the health care.
Keywords: home hospitalization; social work; social intervention